Determinants of the Profitability of Islamic Rural Banks During Covid-19 in Indonesia - Deni Lubis; Dini Arsyi Anjani; Tita Nursyamsiah (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The Return on Asset (ROA) value of Islamic rural banks (BPRS) keeps decreasing during the Covid-19 pandemic, specifically from 2020 to 2021. The ROA value of Sharia Commercial Bank and Sharia Business Unit also decreased in 2020 but increased in 2021. During the pandemic, many financial institutions were in trouble, but BPRS was still able to survive in the midst of a crisis. This phenomenon attracted some scholars to study the factors that made BPRS survive during a pandemic. This study aims to analyze the effect of internal and external factors on Islamic rural banks’ profitability from the second quarter of 2020 to the first quarter of 2022. The sample used consisted of 134 Islamic rural banks with complete data to be analyzed. This study used panel data regression with ROA as the dependent variable. The result of regression shows that partially, FDR has a positive impact on ROA, whereas NPF and OER hurt ROA. On the other hand, CAR, GDP, and CPI have no impact on ROA. The finding shows that the internal factors of the BPRS have an important role in dealing with crises during a pandemic. The government is expected to support the digital transformation of BPRS in order to increase the efficiency and convenience of BPRS, so the public is attracted to join BPRS.